Minocycline Enhances the Effectiveness of Nociceptin/Orphanin FQ during Neuropathic Pain. (3rd September 2014) - Popiolek-Barczyk, Katarzyna; Rojewska, Ewelina; Jurga, Agnieszka M.; Makuch, Wioletta; Zador, Ferenz; Borsodi, Anna; Piotrowska, Anna; Przewlocka, Barbara; Mika, Joanna
Abstract : Nociceptin/orphanin FQ (N/OFQ) antinociception, which is mediated selectively by the N/OFQ peptide receptor (NOP), was demonstrated in pain models. In this study, we determine the role of activated microglia on the analgesic effects of N/OFQ in a rat model of neuropathic pain induced by chronic constriction injury (CCI) to the sciatic nerve. Repeated 7-day administration of minocycline (30 mg/kg i.p.), a drug that affects microglial activation, significantly reduced pain in CCI-exposed rats and it potentiates the analgesic effects of administered N/OFQ (2.5–5  μ g i.t.). Minocycline also downregulates the nerve injury-induced upregulation of NOP protein in the dorsal lumbar spinal cord. Our in vitro study showed that minocycline reduced NOP mRNA, but not protein, level in rat primary microglial cell cultures. In [ 35 S]GTP γ S binding assays we have shown that minocycline increases the spinal N/OFQ-stimulated NOP signaling. We suggest that the modulation of the N/OFQ system by minocycline is due to the potentiation of its neuronal antinociceptive activity and weakening of the microglial cell activation. This effect is beneficial for pain relief, and these results suggest new targets for the development of drugs that are effective against neuropathic pain.